2010
DOI: 10.1111/j.1469-8986.2010.00982.x
|View full text |Cite
|
Sign up to set email alerts
|

Looking at emotional words is not the same as reading emotional words: Behavioral and neural correlates

Abstract: Recent research suggests that the allocation of attentional resources to emotional content during word processing might be sensitive to task requirements. This question was investigated in two tasks with similar instructions. The stimuli were positive, negative, and neutral nouns. Participants had to identify meaningful words embedded in a stream of non-recognizable stimuli (task 1) or pseudowords (task 2). Task 1 could be successfully performed on the basis of the perceptual features whereas a lexico-semantic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

25
113
0
6

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(155 citation statements)
references
References 67 publications
(116 reference statements)
25
113
0
6
Order By: Relevance
“…For instance, Schacht and Sommer 2009a using a lexical decision task reported an EPN in the same time range as it was observed in the present study. It has been previously argued that the degree of linguistic processing modulates the direction of attention to the affective content during word processing reflected in the EPN (Hinojosa et al, 2010;Kissler et al, 2007;Schacht & Sommer, 2009b). Thus, it could be argued that only minimal linguistic processing as in passive reading tasks will lead to faster lexical access as compared to elaborate lexical-semantic processing required in previous studies using a similar task (Palazova et al, 2011;Schacht & Sommer, 2009a,b).…”
Section: Discussionmentioning
confidence: 96%
“…For instance, Schacht and Sommer 2009a using a lexical decision task reported an EPN in the same time range as it was observed in the present study. It has been previously argued that the degree of linguistic processing modulates the direction of attention to the affective content during word processing reflected in the EPN (Hinojosa et al, 2010;Kissler et al, 2007;Schacht & Sommer, 2009b). Thus, it could be argued that only minimal linguistic processing as in passive reading tasks will lead to faster lexical access as compared to elaborate lexical-semantic processing required in previous studies using a similar task (Palazova et al, 2011;Schacht & Sommer, 2009a,b).…”
Section: Discussionmentioning
confidence: 96%
“…For example, affectively valenced words have been reported to provoke larger neural responses in the amygdala than their neutral counterparts (Herbert et al, 2009). In addition, the results of several studies that have used event-related potentials (ERPs) suggest that the emotional content of words modulates brain activity at several temporal stages (Herbert et al, 2008;Hinojosa, Méndez-Bertolo, & Pozo, 2010;Kissler et al, 2007;Schacht & Sommer, 2009;Scott et al, 2009).…”
mentioning
confidence: 99%
“…A significant number of studies have revealed that these effects are pervasive. Indeed, modulations of the processing of words by their emotional content have been documented not only in tasks involving affective decisions (Estes & Verges, 2008;González-Villar, Triñanes, Zurrón, & Carrillo-de-la-Peña, 2014;Herbert, Kissler, Junghöfer, Peyk, & Rockstroh, 2006), but also in experimental situations in which the emotional content was irrelevant to the task (González-Villar et al, 2014;Hinojosa, Méndez-Bértolo, & Pozo, 2010;Kousta, Vinson, & Vigliocco 2009;Schacht & Sommer, 2009;Scott, O'Donnell, & Sereno 2014).…”
mentioning
confidence: 99%
“…emotion and language has taken advantage of the fact that words can be characterized according to these dimensions (Bradley & Lang, 1999). Hence, studies in the field have focused on testing the effects of the valence and arousal of words with different experimental paradigms and tasks, such as the detection of meaningful words in streams of stimuli (Hinojosa et al, 2010), the lexical decision task (Citron, Weekes, & Ferstl, 2013;Kousta et al, 2009;Recio, Conrad, Hansen, & Jacobs, 2014), the affective categorization task (Estes & Verges, 2008), or the emotional Stroop task (González-Villar et al, 2014), among others.…”
mentioning
confidence: 99%